Lipalja vas in njena slovenska govorica - Grošelj, Robert (Linguistica et philologica, 2016)
The monograph ('Lipalja Vas and Its Slovenian Speech') presents a detailed and methodologically sophisticated description of the Zilja local dialect of Slovenian as spoken by its last speakers in the northwestern most part of the Slovenian ethnic territory.The introductory contribution ('Lipalja Vas 200 Years Ago: The Home of Kovači, Trinki and Temmli') authored by a historian and writer Vlado Klemše portrays Lipalja vas at the beginning of the 19th century on the basis of toponyms from the Franciscean cadastre. Karmen Kenda-Jež's contribution ('Spoken Texts from Lipalja Vas'), which was prepared in collaboration with Robert Grošelj and Vera Smole, is the first detailed linguistic analysis of the Slovenian local dialect of Lipalja vas. It provides a commented selection of texts recorded at the research camp in 2005 written in Slovenian dialect transcription.